Training, Strengthening and Development of School Organizations Based on Entrepreneurship - Didin Hadi Saputra; M. Nasuhi; Dhandi Hidayatullah; Mikyarul Ilmy; Hidayatullaely Hidayatullaely; Eka Mayani; Wandi Wasis; Hilmiah Hilmiah; Mulyawarman Saputra; Ihwandi Ihwandi; Endang Sri Wardani (Jurnal Humanities Pengabdian Kepada Masyarakat, 2020)
Implementation of community service activities for Higher Education Institutions is a necessity and an obligation. This is the breath of an academic activity in the Tri Dharma College. This service was attended by representatives of academics, students and service partners of the University of Nahdlatul Wathan Mataram, namely Madrasah Aliyah Nahdlatul Wathan Lenek Lauk, the purpose of this service was to foster independence in applying science in the community. The solution offered by the service team is to provide ongoing assistance for partners, namely student organizations in the target schools. The method used is to provide assistance during activities, and continue activities that have not been completed with further activities. The activity began with the introduction of each member of the service, and introduced the aims and objectives of the service itself, namely for training, development, and challenges in community development in the fostered partner school of the Faculty of Administrative Sciences, Nahdlatul Wathan University, Mataram. In this dedication activity, it gives a pretty good hope, especially for partners, namely learning how to become an agent or pilot location in each service held by the Faculty of Administrative Sciences, Nahdlatul Wathan University, Mataram